Salam Betawi Punya Aye: Brand Awareness Development Strategy For Visitors of KPB Betawi Setu Babakan - Aprilia, Lu’luwatin Rosdiana; Putra, Bagus Alifiano; Chofifah, Marthika Nour (Universitas Negeri Medan, 2024)
This study explores strategies for developing visitor brand awareness through the use of